DEVELOPMENT AND IMPLEMENTATION OF AUTOMATIC SOLAR-POWERED STREETLIGHT SYSTEM FOR A UNIVERSITY CAMPUS - Ariba, Folashade Olamide; Adebanji, Bankole; Ajayeoba, Ayooluwatomiwa Enoch; Adenihun, Emmanuel Oluwatomiwa; Adekeye, Olumide Paul (FUDMA JOURNAL OF SCIENCES, 2026)
Streetlight system is an important feature in modern development to address the problem of night-time insecurity. The existing streetlight system, which uses incandescent bulbs to address this problem, has resulted in energy wastage. This work developed and implemented a solar-powered automatic street light system at Landmark University Omu-Aran campus, intending to optimize energy consumption, while providing enough illumination. The system incorporates; a light sensor, Arduino microcontroller, motion detection and Light Emitting Diode (LED) units for intelligent operation and optimal energy utilization. The system’s electric circuitry was designed using PROTEUS software. Arduino IDE was used to develop a code to help the Arduino microcontroller module interact with the system by controlling the motion and ambient light sensors. Motion sensors were employed with Passive Infrared (PIR) sensors to detect human presence, enabling the system to adjust lighting levels dynamically based on real-time traffic and pedestrian movements, enhancing safety and security. The system utilizes solar photovoltaic panels to harvest renewable energy from the sun, making it environmentally sustainable and cost-effective. Also, Light Detecting Resistor (LDR) light sensors were used to facilitate automatically adjusting illumination levels according to environmental conditions, ensuring optimal visibility while conserving energy during nighttime. However, the developed streetlight prototype was implemented and tested in the Landmark University Omu-Aran campus to determine its optimal energy efficiency over High-Pressure Sodium (HPS) and LED-based streetlight systems. The result shows that the developed solar-powered automatic street light reduced power usage by providing an optimal energy-saving option.